Women in Obasá’s Poetry - Ayoola Oladunnke Aransi; Hakeem Olawale (Yoruba Studies Review)
Obasá’s creativity cuts across virtually all aspects of Yorùbá socio-cultural ̣ settings and his works have attracted the attention of various scholars. It is evident that his poems are laden with topical issues that are of national interest. Most of his works, as described by previous scholars, are based on his love for and interest in Yorùbá language, social values, language, style, cultural practices, and the recovery endangered Yoruba oral art (Babalolá 1971, ̣ 1973; Olábimtán 1974a, 1974b; Ògúnsínà 1980; O ̣ látúnji 1982; Akínye ̣ mí 1987, ̣ 1991, 2017; and Nnodim 2006). Tis essay focuses on the representation of women in Obas ̣ á’s poetry, a topic that has not been given adequate attention. ̣ The essay attempts a close reading of Obas ̣ á’s poems within the Feminism and ̣ womanism theoretical frameworks. The research reveals that the representation of women in the poetry of Obasa did not go beyond the stereotypical and derogatory portrayal of women among the Yoruba.